Catechumens in the East in the Light of Pseudo-epigraphic Normative Church Sources from the 4th Century - Hołasek, Andrzej R. (Studia Ceranea, 2018)
The article discusses the requirements that 4th-century catechumens in the East were expected to meet. Accordingly, the pseudo-epigraphic Church regulations found in the Canons of Hippolitus and in the Apostolic Constitutions are analysed. It can be seen from these texts that their authors showed considerable concern for maintaining high standards associated with the period of the catechumenate; furthermore, they put considerable emphasis on the adherence to the Church regulations and the implementation of Christian standards of thought in daily life.